Assessment of the Implementation of Central Bank of Nigeria Foreign Exchange Policy in Promoting Economic Growth in Nigeria - Ngbede, Adeyi; Itodo, Sylvanus Mohammed; Asomba, Charles Ifeanyi (Kashere Journal of Politics and International Relations, 2025)
This study examines the implementation of the Central Bank of Nigeria's (CBN) foreign exchange policy and its effectiveness in promoting economic growth in Nigeria. Through qualitative research combining content and document analysis, the study evaluates policy documents, economic reports, and institutional data from 2015 to 2023. The research particularly focuses on assessing the effectiveness of CBN's foreign exchange policies in promoting sustainable economic growth and analyzing the impact of forex market distortions on investment patterns and overall economic performance. Findings reveal that while the introduction of the Investors' and Exporters' (I&E) window in 2017 initially attracted significant foreign investment (approximately $20 billion in its first year), the overall effectiveness of forex policies has been mixed. The agricultural sector demonstrated resilience with 3.2% average annual growth, while the manufacturing sector experienced volatility, contracting by 1.5% during periods of significant exchange rate fluctuations. Foreign exchange reserves fluctuated considerably, peaking at $45.1 billion in June 2019 before declining to $33.8 billion by December 2020, affecting the CBN's capacity to maintain exchange rate stability.The study concludes that while CBN's forex policies achieved some success in maintaining exchange rate stability and supporting key economic sectors, their effectiveness in promoting sustainable economic growth was limited by external shocks, structural economic constraints, and implementation challenges. Recommendations include implementing targeted sector-specific support measures and enhancing coordination between monetary policy and fiscal initiatives to create a more coherent framework for sustainable economic growth